Active Commuting and Multiple Health Outcomes: A Systematic Review and Meta-Analysis - Dinu, Monica; Pagliai, Giuditta; Macchi, Claudio; Sofi, Francesco (Sports medicine (Auckland), 2019)
Background Active commuting is associated with greater physical activity, but there is no consensus on the actual beneficial effects of this type of physical activity on health outcomes. Objective To examine the association between active commuting and risk of all-cause mortality, incidence and mortality from cardiovascular diseases, cancer and diabetes through meta-analysis. Methods A comprehensive search of MEDLINE, Embase, Google Scholar, Web of Science, The Cochrane Library, Transport Research International Documentation database, and reference lists of included articles was conducted. Only prospective cohort studies were included. Results Twenty-three prospective studies including 531,333 participants were included. Participants who engaged in active commuting had a significantly lower risk of all-cause mortality [relative risk (RR) 0.92, 95% CI 0.85–0.98] and cardiovascular disease incidence (RR 0.91; 95% CI 0.83–0.99). There was no association between active commuting and cardiovascular disease mortality and cancer. Participants who engaged in active commuting had a 30% reduced risk of diabetes (RR 0.70; 95% CI 0.61–0.80) in three studies after removal of an outlying study that affected the heterogeneity of the results. Subgroup analyses suggested a significant risk reduction (− 24%) of all-cause mortality (RR 0.76; 95% CI 0.63–0.94) and cancer mortality (− 25%; RR 0.75; 95% CI 0.59–0.895) among cycling commuters. Conclusion People who engaged in active commuting had a significantly reduced risk of all-cause mortality, cardiovascular disease incidence and diabetes.